1994
DOI: 10.1111/j.1365-2052.1994.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA fingerprinting in roe deer using the digoxigenated probe (GTG)5

Abstract: Summary The digoxigenin‐labelled oligonucleotide (GTG)5 was used as a multilocus probe to detect hypervariable microsatellites in roe deer DNA digested with Hae III. The resulting fingerprints of 24 animals belonging to four subpopulations were characterized with regard to within‐subpopulation as well as between‐subpopulation similarity. The mean number of polymorphic fragments was 20 and the average band‐sharing rate for unrelated animals 0.27. A mean probability of 91.5% for a fragment to be present in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Postma et al (2001) using the same set of microsatellite loci as in our study on several introduced populations of roe deer in the Netherlands found a highly significant differentiation attributable to the divergent history of the populations and reduced migration over the highly urbanized landscape. Morsch and Leibenguth (1994) using neutral DNA markers, presented a similar conclusion based the absence of a significant differentiation between roe deer populations separated as far as 40 km apart by fenced highways and urban areas. In our study, the Nemunas and Neris rivers are ice free and could slow migration contributing to the genetic structure observed in our study.…”
Section: Geographic Location Effect On the Genetic And Morphometric Vsupporting
confidence: 60%
“…Postma et al (2001) using the same set of microsatellite loci as in our study on several introduced populations of roe deer in the Netherlands found a highly significant differentiation attributable to the divergent history of the populations and reduced migration over the highly urbanized landscape. Morsch and Leibenguth (1994) using neutral DNA markers, presented a similar conclusion based the absence of a significant differentiation between roe deer populations separated as far as 40 km apart by fenced highways and urban areas. In our study, the Nemunas and Neris rivers are ice free and could slow migration contributing to the genetic structure observed in our study.…”
Section: Geographic Location Effect On the Genetic And Morphometric Vsupporting
confidence: 60%
“…Figure 1 shows the fingerprints of 11 specimens of the Wustweiler subpopulation. Since somatic stability of the restriction fragment pattern was confirmed by preliminary experiments (Morsch & Leibenguth 1993), the organs from which DNA was isolated (spleen or kidney) are not specified. The following roe deer have a known degree of relatedness (r = 0.5): R5 is a 6-month-old female fawn of its mother R4 and R8 (9) and R 9 (6) are embryos of the female R10.…”
Section: Methodsmentioning
confidence: 99%